Synthesis and Characterization of Liquid Crystalline Azobenzene Chromophores with Fluorobenzene Terminal - M. M., Yusoff; Lutfor, M. R.; Hegde, Gurumurthy; Mahrokh, Azazpour; Sandeep, Kumar (Elsevier, 2013)
Two series of fluorine-substituted benzoate ester type rod-shaped liquid crystals incorporating the azobenzene as side arm linked with terminal double bonds as polymerizable functional groups were synthesized and characterized by polarized-light optical microscopy (POM), differential scanning calorimetry (DSC) and UV–visible spectroscopy investigations. Thus, rod-shaped monomers, namely 4a and 4b having odd and even number of carbon in the terminal group exhibited nematic phase and SmA type phase was found at lower temperature. Compound 5 showed nematic phase whereas compound 6 showed SmA phase. These rod-shaped molecules exhibit strong photoisomerization behaviour in solution. The photoswitching properties of the compounds showed trans to cis isomerization in about 10 s, whereas the reverse process takes place about 120 min in solutions. Proposed materials may have potential to use it in optical storage devices.